ANTIMICROBIAL ANALYSIS OF DIFFERENT PARTS EXTRACT IN DIFFERENT SOLVENT SYSTEM OF A WASTE WEED - CALOTROPIS PROCERA. - Kar, Dattatreya; Pattanaik, Pratap Keshari; Pattnaik, Bibhudutta; Kuanar, Ananya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: In the current study, we have focused on the major secondary metabolite containing parts such as flower, leaf, and root for phytochemical extraction with three different solvent systems to make a comparative study against three virulent bacteria species which are capable of intestinal infection, pneumonia, skin infections, and food poisoning. Methods: Antimicrobial activity of ethanol, methanol, and chloroform extracts from bark, leaves and roots of Calotropis procera, was examined against three virulent bacteria species: Escherichia coli, Staphylococcus aureus, and Bacillus subtilis using disc diffusion method. Results: The ethanol extract of leaf showed significant activity against S. aureus with a zone of inhibition ranging from 14 to 20 mm for S. aureus. The ethanol extract of flower was effective against E. coli with maximum 18 mm. Ethanol extract of root showed significant activity against S. aureus. Methanol extract of leaves showed moderate activity against S. aureus with a zone of inhibition ranging from 14 to 20 mm. Methanol extract of root showed significant activity against S. aureus with a zone of inhibition ranging from 12 to 22 mm. Methanol extract of flowers showed activity against E. coli with a zone of inhibition ranging from 11 to 20 mm. The chloroform extract of leaves showed significant activity against S. aureus. Chloroform extract of flower showed activity with zone of inhibition ranging from 11 to 17 mm for S. aureus chloroform extract of root showed activity against E. coli with zone of inhibition ranging from 9 to 17 mm. Conclusion: From the above study, it can be concluded that the activity of the plant extract may be due to the secondary metabolites or broad-spectrum antibiotic compounds present in it.